NRF2 Exerts Anti-Inflammatory Effects in LPS-Induced gEECs by Inhibiting the Activation of the NF-κB - Hongchu Bao; Qinglan Qu; Wei Zhang; Xinrong Wang; Jianye Fang; Jinwen Xue; Zhenteng Liu; Shunzhi He (Mediators of Inflammation)
Nuclear factor E2-related factor 2 (NRF2) plays an anti-inflammatory role in several pathological processes, but its function in lipopolysaccharide- (LPS-) induced goat endometrial epithelial cells (gEECs) is still unknown. We designed a study to investigate the function of NRF2 in LPS-induced gEECs. LPS was found to increase the NRF2 expression and the nuclear abundance of NRF2 in gEECs in a dose-dependent manner. NRF2 knockout (KO) not only increased the expression of LPS-induced proinflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-8) but also increased the expression of TLR4, p-IκBα/IκBα, and p-p65/p65 proteins. Immunoprecipitation experiments showed that NRF2 directly binds to p65 in the nucleus and inhibits the binding of p65 to downstream target genes (TNF-α, IL-1β, IL-6, and IL-8). Even though a NF-κB/p65 inhibitor (PDTC) reduced the LPS-induced NRF2 expression and nuclear abundance of NRF2, overexpressing TNF-α reversed the inhibitory effects of PDTC on the NRF2 expression and on its abundance in the nucleus. Similarly, knockdown of the proinflammatory cytokines (TNF-α, IL-1β, IL-6, or IL-8) significantly decreased the LPS-induced NRF2 expression and NRF2 in the nucleus. In conclusion, our data suggest that proinflammatory cytokines induced by LPS through the TLR4/NF-κB pathway promote the NRF2 expression and its translocation into the nucleus. Our work also suggests that NRF2 inhibits the expression of proinflammatory cytokines by directly binding to p65.